Newcastle Disease in Local Chickens of Live Bird Markets and Households in Zamfara State, Nigeria. (16th January 2014) - Jibril, A. H.; Umoh, J. U.; Kabir, J.; Saidu, L.; Magaji, A. A.; Bello, M. B.; Raji, A. A.
Abstract : Newcastle disease constitutes a major constraint to rural poultry production system in Nigeria. This study used serological method to estimate the level of circulating antibodies against ND in nonvaccinated village chickens, raised under traditional management system in Zamfara State, Nigeria. Competitive Enzyme Linked Immunosorbent Assay was used to analyze 504 chicken sera for Newcastle disease virus antibodies from randomly selected households and live bird markets. Higher seroprevalence rate of Newcastle disease virus antibodies was detected in both household and live bird markets. Overall, seropositive rate was found to be 32.5% (164/504). About 35.8% (115/321) sero-positive rate was obtained from live bird markets while 26.8% (49/183) seropositive rate was found in households. Comparison was made between the sero prevalence of house hold and live bird markets as well as between sexes. Live bird markets show a statistically significant higher prevalence rate (P < 0.05 ) when compared with chickens sampled from households (OR 1.53; 95% CI, 1.024–2.275). The prevalence of ND indicated the presence of the virus amongst the population, and hence there should be an improvement in the vaccine campaign against ND for rural poultry especially the use of thermostable vaccine to reduce the chances of vaccine failure.